2018
DOI: 10.1002/jcb.26901
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR enhanced paclitaxel and doxorubicin resistance in gastric cancer cells partly through inhibiting miR‐217 expression

Abstract: Drug resistance is a big obstacle for clinical anti-tumor treatment outcome. However, the role of HOTAIR in drug resistance in gastric cancer (GC) remains unknown. In this study, we showed that overexpression of HOTAIR enhanced paclitaxel and doxorubicin resistance in GC cells. Furthermore, the expression of HOTAIR was upregulated in GC tissues and higher expression of HOTAIR was associated with late stage. In addition, we showed that miR-217 expression was lower in GC tissues compared with the paired non-tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 38 publications
1
45
1
Order By: Relevance
“…A recent study reported that PTPN14 overexpression promotes the proliferation and migration of gastric cancer cells 37 . Moreover, PTPN14 overexpression contributes to the paclitaxel and doxorubicin resistance of gastric cancer cells 38 . These studies indicate that the precise PTPN14 function in tumourigenesis may be cancer‐type dependent.…”
Section: Discussionmentioning
confidence: 88%
“…A recent study reported that PTPN14 overexpression promotes the proliferation and migration of gastric cancer cells 37 . Moreover, PTPN14 overexpression contributes to the paclitaxel and doxorubicin resistance of gastric cancer cells 38 . These studies indicate that the precise PTPN14 function in tumourigenesis may be cancer‐type dependent.…”
Section: Discussionmentioning
confidence: 88%
“…EZH2 is a highly conserved histone methyltransferase that targets lysine-27 of histone H3, which mediates epigenetic regulation in disease progression. Besides severing as a scaffold protein, Hotair was also reported to promote drug resistance in gastric cancer cells partly through inhibiting miR-217 expression 33 , and it also contributes to liver cancer via targeting miR-217. 31 In addition, EZH2 was induced by vascular endothelial growth factor (VEGF) in endothelial cells and thus promoted tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple onco-lncRNAs, such as HOTAIR, CASC9, MRUL, UCA1, D63785, NEAT1 and HULC, are involved in ADR resistance in gastric cancer (Table 9). For example, via inhibiting miR-217 expression, lncRNA HOTAIR can promote ADR resistance of gastric cancer cells [182]. LncRNA cancer susceptibility candidate 9 (CASC9), whose expression is associated with poor differentiation, invasion and lymph node metastases of gastric cancer, has been reported to promote resistance to ADR of gastric cancer cells through up-regulating expression of MDR1 protein [183].…”
Section: Lncrnas and Adr Resistancementioning
confidence: 99%
“…Several miRNAs, lncRNAs and circRNAs have been found to be involved in gastric cancer drug resistance by influencing apoptosis, DNA repair, cell cycle, proliferation, autophagy, epithelial-mesenchymal transition, and cancer stem cell through regulating expression of potential target genes and related signaling pathway [175]. In addition, lncRNAs PVT1 [177], HOTAIR [182] and CASC9 [183] also promoted PTX resistance of gastric cancer through modulating expression of various genes.…”
Section: Lncrnas and Ptx Resistancementioning
confidence: 99%